2015
DOI: 10.1073/pnas.1502875112
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of the human microbiota during pregnancy

Abstract: Despite the critical role of the human microbiota in health, our understanding of microbiota compositional dynamics during and after pregnancy is incomplete. We conducted a case-control study of 49 pregnant women, 15 of whom delivered preterm. From 40 of these women, we analyzed bacterial taxonomic composition of 3,767 specimens collected prospectively and weekly during gestation and monthly after delivery from the vagina, distal gut, saliva, and tooth/ gum. Linear mixed-effects modeling, medoid-based clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

78
1,076
17
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 943 publications
(1,221 citation statements)
references
References 35 publications
(61 reference statements)
78
1,076
17
22
Order By: Relevance
“…G. vaginalis was also one of the six dominant species identified by 16S rRNA gene sequencing in a microbiota community type distinguished by higher cervicovaginal levels of IL-1␣, IL-␤, IL-8, TNF-␣, IFN-␥, and IL-10 in young South Africans at risk of HIV (75). A recent 16S rRNA gene analysis confirmed that a high abundance of Gardnerella in particular, combined with a low abundance of Lactobacillus, may contribute to the increased risk of preterm birth (76). Thus, strong evidence supports the role of G. vaginalis in modifying host immunity and BV pathogenesis.…”
Section: Gardnerella Vaginalismentioning
confidence: 91%
“…G. vaginalis was also one of the six dominant species identified by 16S rRNA gene sequencing in a microbiota community type distinguished by higher cervicovaginal levels of IL-1␣, IL-␤, IL-8, TNF-␣, IFN-␥, and IL-10 in young South Africans at risk of HIV (75). A recent 16S rRNA gene analysis confirmed that a high abundance of Gardnerella in particular, combined with a low abundance of Lactobacillus, may contribute to the increased risk of preterm birth (76). Thus, strong evidence supports the role of G. vaginalis in modifying host immunity and BV pathogenesis.…”
Section: Gardnerella Vaginalismentioning
confidence: 91%
“…in the female lower genital tract may be a risk factor for chorioamnionitis and adverse pregnancy outcomes, such as preterm birth (179)(180)(181)(182)(183)(184). A prospective study of 2,471 women attending an antenatal clinic demonstrated that Ureaplasma spp.…”
Section: Lower Genital Tract Ureaplasma Colonization Association Withmentioning
confidence: 99%
“…Other such illnesses include gastrointestinal cancer (Meurman and Grönroos 2010), breast cancer (Laidi et al 2016), cirrhosis (Bajaj et al 2015), and diabetes (Maruyama et al 2007;Deshpande et al 2010;Farag and Gaballa 2011). More recently, links with pregnancy (Digiulio et al 2015), the human immunodeficiency virus (HIV) (Kistler et al 2015), and acquired immune deficiency syndrome (AIDS) have also been described (Zheng et al 2015).…”
Section: The Huat Microbiota and General Disordersmentioning
confidence: 99%